Genetic and pharmacological inhibition of two‐pore domain potassium channel TREK‐1 alters depression‐related behaviors and neuronal plasticity in the hippocampus in mice. (30th August 2020) - Wu, Fangfang; Sun, Hongbin; Gong, Weigang; Li, Xiaoli; Pan, Zhaohui; Shan, Han; Zhang, Zhijun
Abstract: Introduction: The two‐pore domain potassium channel TREK‐1 is a member of background K + channels that are thought to provide baseline regulation of membrane excitability. Recent studies have highlighted the putative role of TREK‐1 in the action of antidepressants, and its antagonists might be potentially effective antidepressants. However, the mechanisms underlying the actions of TREK‐1 are not yet fully understood. Methods: The expression of TREK‐1 was examined in a mouse model of chronic unpredictable mild stress (CUMS) using immunoblotting. Neuron‐specific genetic manipulation of TREK‐1 was performed through adeno‐associated virus. Behavioral tests were performed to evaluate depression‐related behaviors. Electrophysiological recordings were used to evaluate synaptic plasticity. Golgi staining was used to examine neuroplasticity. Results: TREK‐1 expression was increased in the mouse hippocampus after CUMS. Knockdown of TREK‐1 in hippocampal neurons significantly attenuated depressive‐like behaviors and prevented the decrease of CUMS‐induced synaptic proteins in mice. Further examination indicated that neuron‐specific knockdown of TREK‐1 in the hippocampus prevented stress‐induced impairment of glutamatergic synaptic transmission in the CA1 region. Moreover, chronic TREK‐1 inhibition protected against CUMS‐induced depressive‐like behaviors and impairment of synaptogenesis in the hippocampus. Conclusion: Our results indicate a role for TREK‐1 in the modulation of synaptic plasticity in a mouse model of depression. These findings will provide insight into the pathological mechanism of depression and further evidence for a novel target for antidepressant treatment. Abstract : TREK‐1 channel in the hippocampus is essential for depressive‐like behaviors in response to the CUMS‐induced anhedonia model of depression. This study demonstrated the modulatory effect of TREK‐1 on dendrite morphology, dendrite spine density, glutamatergic synaptic transmission, and synaptogenesis in the hippocampus. TREK‐1 is involved in the pathogenesis of depression by regulating neuronal plasticity.